Forage maize : production and utilisation - Bunting, E.S. (London : Agricultural Research Council, 1978)
This book is a study of the various aspects of breeding, agronomy, conservation and utilization of this crop and brought the present state of knowledge of the production and use of maize.
Including bibliographical references and index.
osa 21/01/2019
Loans
Keywords: Corn; Europe